2021
DOI: 10.3390/membranes11090662
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Research and Application of Nanofiltration (NF) Technology for Brackish Water Treatment

Abstract: Brackish water is a potential fresh water resource with lower salt content than seawater. Desalination of brackish water is an important option to alleviate the prevalent water crisis around the world. As a membrane technology ranging between UF and RO, NF can achieve the partial desalination via size exclusion and charge exclusion. So, it has been widely concerned and applied in treatment of brackish water during the past several decades. Hereon, an overview of the progress in research on and application of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 135 publications
1
19
0
4
Order By: Relevance
“…The enhanced surface hydrophilicity of the fumed silica zeolite NF membranes attract more water molecules close to the membrane than those of colloidal silica zeolite NF membranes, and facilitated the transport of water molecules in the membrane, which is an observed phenomenon here in line with most reported work [51,97,98]. Also, the diffusion affinity seems to be of great interest probably due to the nature of both zeolites resulting from different silica sources used.…”
Section: Flux Analysissupporting
confidence: 85%
“…The enhanced surface hydrophilicity of the fumed silica zeolite NF membranes attract more water molecules close to the membrane than those of colloidal silica zeolite NF membranes, and facilitated the transport of water molecules in the membrane, which is an observed phenomenon here in line with most reported work [51,97,98]. Also, the diffusion affinity seems to be of great interest probably due to the nature of both zeolites resulting from different silica sources used.…”
Section: Flux Analysissupporting
confidence: 85%
“…The commercial membrane NF90 was investigated in order to study its efficiency to remove fluoride from brackish waters [69]. The results showed that the rejection rate of the membrane was stabilized at a pressure of 11 bar.…”
Section: Polymer Membranesmentioning
confidence: 99%
“…Among these techniques, membrane separation has attracted a great deal of attention, especially for the removal of small organic molecules and high-valence inorganic salts [ 2 , 3 , 4 , 5 ]. Studies of membranes have aided in the development of various research fields, including wastewater treatment [ 6 , 7 , 8 , 9 ], the pharmaceutical industry [ 10 , 11 , 12 ], food processing [ 13 , 14 ], and bioengineering [ 15 , 16 ]. During the separation process, both steric hindrance and the electrostatic repulsion effect determine the specific performance of a membrane [ 17 ].…”
Section: Introductionmentioning
confidence: 99%